Improvement of organization of marketing service in textile enterprises - Musayeva Shoira Azimovna, (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In this article, the integrated indicator of complex competitiveness, which includes resource competitiveness, investment, innovation, technological, marketing and logistics, management competitiveness, is discussed.